The Use Of Conventional Banks By Sharia Economic Law Students: Practice, Factors, And Laws - Thamrin, Dzaky Adam; Athief, Fauzul Hanif Noor (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2020)
This study aims to reveal the factors and reasons behind the large number of Islamic Economic Law students using conventional banks which are then analysed with an Islamic law approach.The method used in this study is descriptive quantitative and qualitative study. Data collection by survey and interview methods. The data analysis used descriptive and deductive analysis approach.The results of this study found that most students use conventional banks, although half of them are aware of the concern of usury on interest. Nevertheless, in practice, only a small percentage of them separate bank interest from their savings. The majority of the reasons they use conventional banks are based on facilities, family and work. Under Islamic law, the use of conventional banks is haram, although there are cases where it is permissible under Islamic law.